Relationship Between Low Education and Poor Periodontal Status among Mexican Adults Aged ≥50 Years - Garcia Perez, Alvaro; Cuevas-González, Juan Carlos; Rodriguez Chavez, Jacqueline Adeline; Rodriguez Gonzalez, Kathia Guadalupe; VILLANUEVA GUTIERREZ, TERESA; Velazquez Olmedo, Laura Barbara; Moreno Altamiranos, Alejandra (2024)
Purpose: To examine the association between educational level and the presence of periodontal disease in adults ages ≥ 50 years in Mexico. Materials and Methods: A cross-sectional study was conducted on 2098 Mexican adults, using data from the annual reports of the Epidemiological Monitoring System for Oral Pathologies from 2019–2022. Data were collected on sociodemographic characteristics such as gender, age, educational level, oral hygiene, and diabetes.